Cinnamaldehyde-modified chitosan hybrid nanoparticles for DOX delivering to produce synergistic anti-tumor effects - Zhou, Zuoqin; Wang, Caiyun; Bai, Jingqi; Zeng, Zihan; Yang, Xiaoyu; Wei, Bing; Yang, Zheng (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer cells are under oxidative stress associated with the increased generation of reactive oxygen species (ROS). Therefore, increasing the oxidative stress of tumor cells by delivering ROS generators is an effective strategy to induce apoptosis of cancer cells. Herein, we reported a hybrid nanoparticle based on lactobioic acid (LA) modified chitosan and cinnamaldehyde (CA) modified chitosan, which possess both active tumor-targeting ability and ROS regulation ability, in order to have a synergistic effect with the anti-tumor drug doxorubicin (DOX). LA can improve the tumor-targeting ability and cellular accumulation of these nanoparticles, and CA can induce apoptotic cell death through ROS generation, mitochondrial permeability transition and caspase activation. The particle size and distribution as well as drug release profiles of these nanoparticles were observed. In vitro and in vivo antitumor studies demonstrated that the hybrid nanoparticles show significant synergistic antitumor effect. Thus, we anticipate that the hybrid nanoparticles have promising potential as an anticancer drug carrier.